Genetic variability in food-type soybean accessions assessed by morphoagronomic traits - Zeffa, D. M.; Perini, L. J.; Freiria, G. H.; Silva, G. M. da; Gomel, G. R.; Constantino, L.; Alves, S. M.; Koyama, R.; Oliveira Neto, S. S. de [UNESP] (Funpec-editora, 2019)
The estimation of genetic variability in germplasm banks is important not only for the conservation of genetic resources, but also for their use in plant breeding. However, a large number of traits from different categories (qualitative and quantitative) can make the analysis and interpretation of the results difficult, often resulting in an incomplete distinction among accessions. We characterized 45 accessions of food-type soybean (Glycine max) from the Soybean Germplasm Bank of Londrina State University based on morphoagronomic traits. The experiment was carried out in the university farm using a randomized block design with three replicates. Twelve traits were evaluated: flower color, pubescence color, tegument color, hilum color, days until flowering, days until maturation, plant height, height of insertion of the first pod, mass of 100 grains, grain yield per plot, agronomic value, and lodging index. The quantitative trait data were submitted to deviance analysis. The genetic divergence among the accessions was examined by Gower's distance and clustering of the accessions was made based on Ward's hierarchical method. Morphoagronomic descriptors proved efficient in detecting the levels of genetic variability among the accessions maintained in the germplasm collection. Gower's distance was efficient in the discrimination of accessions, showing that simultaneous analysis of quantitative and qualitative traits is useful to evaluate the variability in a germoplasm bank. These results can be used as an additional source of information to be exploited in food-type soybean breeding programs.
Keywords: Glycine max; Multivariate analysis; Morphoagronomic descriptors; Gower's distance